2018
DOI: 10.29122/jtl.v19i2.2840
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down and Bottom-Up Method on Measuring CO2 Emission from Road-Based Transportation System (Case Study: Entire Fuel Consumption, Bus Rapid Transit, and Highway in Jakarta, Indonesia)

Abstract: ABSTRAKSistem transportasi darat berbasis jalan di Jakarta memberikan kontribusi tertinggi dalam inventarisasi emisi CO2 DKI Jakarta sebesar 45% dengan jumlah 19,61 juta ton CO2 pada tahun 2005. Meskipun ada beberapa strategi pada berbagai peraturan, kebijakan, dan kegiatan yang mengarah pada pengurangan emisi CO2, tata kelola hal-hal tersebut terpecah dalam hal mendefinisikan metode yang dapat diandalkan dalam mengukur emisi CO2 dari sektor transportasi berbasis jalan darat. Pendekatan top-down yang digunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…co.id), focusing on used cars and motorbikes sold in DKI Jakarta. VKT of buses and trucks was derived from the previous research conducted by Adhi (2018). Under the regulations of the Indonesian Government, emissions standards are differentiated only by vehicle category and not by vehicle age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…co.id), focusing on used cars and motorbikes sold in DKI Jakarta. VKT of buses and trucks was derived from the previous research conducted by Adhi (2018). Under the regulations of the Indonesian Government, emissions standards are differentiated only by vehicle category and not by vehicle age.…”
Section: Methodsmentioning
confidence: 99%
“…Before moving forward on whether the change from Euro 2 to Euro 4 will result in better air quality in DKI Jakarta, identifying and understanding the significant contributors to the current air pollution is crucial. Most studies in Indonesia calculated CO 2 emissions using total fuel consumption (Batjargal, 2017, Adhi et al, 2018, and PT. Delima Laksana Tata, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The formula was further modified by Adhi (2018), to suit the study as shown in Equation 3. The primary data requirements for this approach include:…”
Section: Ghg Emissions Of a Transport Activity = Transport Activity ×...mentioning
confidence: 99%
“…Mass transit lines usually have established routes and hours, which is why it is possible to plan a battery charging system to maintain the highest possible uptime of the service [16][17][18]; this is one of the reasons why public transport operators are increasingly opting for tailor-made solutions that guarantee the highest energy efficiency per passenger [19,20]. Among the tests performed, those of fuel or energy consumption have become particularly prevalent with the existing global urgency to reduce CO 2 emissions [21,22]. For example, Hu et al conducted an analysis two different energy management strategies and battery sizes, where smaller batteries represented less energy consumption by fewer passengers carried as system uptime decreased [23].…”
Section: Introductionmentioning
confidence: 99%